Consensus on managing delayed methotrexate elimination in high-dose therapy: insights from the Middle East - Al Manasour, Mubarak; Absi, Ahmad; Alhuraiji, Ahmad; Khanani, Muhammad Faisal; Mheidly, Kayane; Elsaid, Mohamed; Ballourah, Walid; Al-Khabori, Murtadha; Al Zain, Naser; Khalifa, Nisreen; Rihani, Rawad; Abdallah, Shaker; et al. (Frontiers in Oncology, 2025)
IntroductionHigh-dose methotrexate (HDMTX) therapy is a cornerstone in treating pediatric and adult cancers, namely, acute lymphoblastic leukemia, non-Hodgkin lymphoma, and osteosarcoma, due to its capability to penetrate the blood–brain barrier. Despite its therapeutic benefits, HDMTX poses significant risks of delayed methotrexate elimination (DME) and associated toxicities such as acute kidney injury (AKI). These risks necessitate individualized dosing and preventive strategies, including hyperhydration, urine alkalinization, and leucovorin rescue.MethodsTo address these challenges, a modified Delphi method with two rounds was used to develop consensus statements to guide clinicians in mitigating HDMTX-associated toxicities and optimizing management strategies. A panel of 13 experts from Saudi Arabia, United Arab Emirates (UAE), Kuwait, Oman, Jordan, and Egypt formulated 54 initial statements focusing on HDMTX regimens, risk factors, preventive care, and monitoring strategies.ResultsConsensus (≥75%) was reached on 50 statements covering HDMTX regimens, preventive care, and toxicity management. Recommendations emphasized standardized methotrexate monitoring intervals, structured risk assessment for DME and AKI, supportive care measures (hyperhydration, urine alkalinization), pharmacokinetically adjusted leucovorin rescue, and the role of glucarpidase in severe toxicity or AKI.ConclusionsThis consensus provides concrete clinical strategies for the safe and effective use of HDMTX, including structured risk stratification for DME, standardized monitoring intervals, pharmacokinetically guided leucovorin adjustments, and early glucarpidase intervention in patients with AKI or severe toxicity. These recommendations are particularly relevant for optimizing HDMTX administration in regions with limited access to advanced interventions.